PHARMACOECONOMIC ASPECTS OF THE PREVENTION OF VENOUS THROMBOEMBOLIC EVENTS AFTER LARGE JOINTS REPLACEMENT - A. V. Rudakova (Столичная издательская компания, 2015)
Venous thromboembolic (VTE) events are a major concern in large joints replacement leading to patients' death. The prevention of VTE events suggests the prescription of low molecular weight heparin or oral anticoagulants that differ significantly in their efficacy, safety and cost of the therapy. Aim. To assess the cost-effectiveness of different options for the prevention of VTE events in hip and knee joints replacement. Material and methods. The model, which allows evaluation of the VTE complications incidence in patients aged 60-65years, was developed based on the results of such clinical trials as ADVANCE-2, ADVANCE-3, RE-MODEL, RE-NOVATE. Analysis was performed on survival period of patients. Weighted average prices of public bidding for the purchase of drugs (enoxaparin, dabigatran and apixaban) during the first quarter of 2015 were the source of the data on the expenses on VTE events prevention. The cost of treatment of VTE events matched for the rate of compulsory health insurance in St. Petersburg for 2015. The costs and life expectancy of patients were discounted at 3.5% per year. Results. The best results for the prevention of VTE events are observed at the treatment regimen with apixsaban. Treatment regimens with dabigatran and enoxaparin were less effective and comparable with each other. At that, the prevalence of major bleedings was similar for all treatment regiments. Apixaban reduced the cost of treatment and prevention of VTE events 1.8-2.0 times as compared with enoxaparin and 1.2-1.4 times in comparison with dabigatran. Conclusion. The new oral anticoagulants are effective and safe alternative to low molecular weight heparins used for the prevention of VTE events in large joints replacement and provide budgetary savings as compared with enoxaparin. Apixaban has a maximum capacity for the reduction of VTE events, lowering the cost of treatment and prevention of VTE events.